Análisis del ángulo nasolabial relacionado al tipo de perfil en los y las estudiantes de la Universidad Nacional de Loja, modalidad presencial, periodo mayo-julio del 2014. - Buri Caraguay, Nely Germania (2015)
ABSTRACT Study the standard measure of nasolabial angle as determined Arnett and Bergman, identified the most frequent type of profile by gender, established the relationship between the nasolabial angle with the type of facial profile. This study was descriptive, transversal took place in or on 894 students from the National University of Loja, of which a sample of 79 students of which 45 were male and 34 female was obtained. To collect information profile pictures was used considering the quality standards. It was determined that the standard measure of nasolabial angle according to Arnett and Bergman more prevalent in the students was between 85-105 degrees considered within the norm, in males 78% and females 71%. The angle of facial convexity was more prevalent determines the straight facial profile, 83% men and 72% women. In the relationship of nasolabial angle with straight facial profile was determined that 83% of men and 72% women had a nasolabial angle in the standard. In the concave facial profile was determined that men had a 50% one angle decreased and 50% the nasolabial angle in standard, while women 100% presented the nasolabial angle in the standard. And the convex facial profile to both men and women prevailed nasolabial angle in standard 69% and 60% respectively, while 31% of men and 40% women had a nasolabial angle increased. A direct relationship between the nasolabial angle and facial profile, because the prevailing standard measure of nasolabial angle within the standard and straight facial profile, thereby determining a facial harmony in the students was found. The photographic assessment of facial soft tissue seen in profile are essential to fully understand the aesthetic characteristics of the patient, so it is recommended that the photographs are of quality, to reflect as closely as possible the patient's condition and so to establish later comparisons.